Diversity and biogeographic affinities of sharks, rays and chimaeras (Chondrichthyes: Elasmobranchii, Holocephali) of Mexico - Del Moral Flores, Luis Fernando (2016)
The diversity of chondrychthyans in Mexico is described. The fauna is composed by 214 species (111 sharks, 95 rays and 8 chimaeras) and represents 17.3 % of the total number of species recorded worldwide. The families with the highest diversity comprise: Rajidae (14.5 %), Carcharhinidae (12.1 %), Pentanchidae, Triakidae, and Urotrygonidae (5.1 %). In terms of geographical distribution, the diversity on the Mexican Pacific slope reaches up to 56.1 % of those species inhabiting Mexican marine and brackish waters (120 species, 62 genera, 37 families and 14 orders); the diversity in the Atlantic slope resulted similar to that on the Mexican Pacific with 55.1 % of the species (118 species, 59 genera, 35 families and 13 orders). The biogeographical affinities of the Mexican chondrychthyan fauna are complex with 19.7 % of the species being circumglobal, 9.9 % transatlantic, 1.9 % transpacific, and 9.4 % endemic to the exclusive economic zone. Additionally, 36.6 % of the species recorded so far are endemic to the Eastern Pacific coast where the species are similar to those found in the Cortez biogeographic province (27.7 %), followed by the Californian (20.7 %), Panamanian (19.3 %), Galapagos (5.6 %) and Peruvian-Chilean (8.9 %). Likewise, 33.3 % are endemic of the Atlantic coast, where species are similar to those found in the Caribbean province (31.9 %), followed by the Carolinean (24.4 %) and the Brazilian (6.6 %).